PENGEMBANGAN VIDEO PERANCANGAN DAN PELAKSANAAN PRAKTIKUM BIOLOGI - Oktavia Safitri; Evi Suryawati; Darmadi Darmadi (Program Studi Pendidikan Biologi, 2021)
Regulation of the Minister of National Education of the Republic of Indonesia Number 16 of 2007 concerning Academic Qualification Standards and Teacher Competencies states that one of the competencies of high school biology teachers is the competence to properly design and implement practicum. Biology Education students as prospective biology teachers must master these competencies. The existence of independent learning resources can be used as a reference for prospective student teachers in studying material related to practicum activities. This study aims to produce independent learning resources in the form of videos. This research was conducted at the PMIPA Laboratory FKIP Riau University, SMAN 8 Pekanbaru and SMAN 15 Pekanbaru in April-December 2020. The type of research used was Research and Development (R&D) with the ADDIE model. The instruments used in this study were the validation sheet and response questionnaire. The results of the video validation obtained an average value of 3.57 with a very valid category. The results of the limited trial phase I obtained an average value of 3.64 in the very good category, while the results of the phase II trial obtained an average value of 3.43 in the very good category. Based on the results of the validation and trials, it shows that the video of the design and implementation of the biology practicum developed can be used as an independent learning resource for prospective biology teachers.